Diffuse bone marrow uptake related to granulocyte colony-stimulating factor-producing maxillary sinus carcinoma on 4-borono-2-18F-fluoro-L-phenylalanine positron emission tomography/computed tomography - Kusumahstuti, Kharisma; Watabe, Tadashi; Kitamura, Naoya; Yamamoto, Tetsuya (World Journal of Nuclear Medicine, 2021)
Granulocyte colony-stimulating factor (G-CSF) can be produced by tumor cells and is known to promote tumor growth, thereby potentially accelerating disease progression. Squamous cell carcinoma (SCC) at maxillary sinus is aggressive growth with poor prognosis. Maxillary sinus carcinomas are rare and can be clinically silent in the early stages or manifest with the same signs and symptoms of more common illnesses, leading to their delayed diagnosis of disease. Hypermetabolic uptake of 18F-fluorodeoxyglucose (18F-FDG) but not of 4-borono-2-18F-fluoro-L-phenylalanine (18F-FBPA), in the bone marrow of patients with G-CSF-producing tumors without bone marrow involvement during positron emission tomography (PET), has been reported. The present case report describes our first experience of bone marrow uptake in PET/computed tomography examination using 18F-FBPA, high uptake seen in the bone marrow of a patient with a G-CSF-secreting SCC of the maxillary sinus that it relapsed following chemoradiation therapy and surgical resection of the tumor.
Keywords: 18F-4-borono-2-18F-fluoro-l-phenylalanine; bone marrow uptake; GSF; maxillary squamous carcinoma